Dietary Compliance and Quality of Life in Celiac Disease: A Long-Term Follow-Up of Primary School Screening-Detected Patients - Iorfida, Donatella; Valitutti, Francesco; Vestri, Annarita; Di Rocco, Arianna; Cucchiara, Salvatore; Lubrano, Riccardo; Montuori, Monica (Frontiers in Pediatrics, 2021)
Background: Whether the diagnostic approach for celiac disease (CD) can really affect quality of life (QoL) and dietary compliance remains controversial. Aims: To evaluate QoL and compliance to the gluten free diet (GFD) in adolescents/young adults diagnosed with CD through a screening strategy during childhood compared to age-matched CD patients diagnosed by case-finding. To assess whether follow-up at a referral center for CD influences compliance and QoL. Materials and Methods: Thirty-seven CD patients who were diagnosed by screening programs (SC-group) and 38 age-matched CD patients diagnosed due to symptoms (CF group) were enrolled. Patients were asked to answer a questionnaire on QoL, dietary compliance and follow-up care for CD. Results: Twenty-nine patients of the SC-group (median age 18.0 years, IQR 16.0 – 19.0) and 31 patients of the CF-group (median age 17.0 years, IQR 15.5 - 18.0) completed the questionnaire. No significant difference was shown between the two groups relating adherence to the GFD and QoL. The majority (93.5%) of CF patients regularly had annual follow-up at a referral center compared to 37.9% of the SC-group (p < 0.001). Conclusion: The diagnostic strategy does not seem to impact QoL and dietary compliance. However, implementation of follow-up might still be necessary for patients identified through screening.